Analysis Of Pipe Welding Quality Control Using The Seven Tools Method In The Manufacturing Industry - Bornon Tapubolon; Hery Irwan (International Journal of Science and Environment (IJSE), 2026)
Weld quality plays an important role in ensuring the reliability and safety of pipe products in the manufacturing industry. Welding defects may increase production costs, require rework, and reduce operational efficiency. This study aims to identify welding defects, determine the dominant defect types, analyze their root causes, and propose quality improvement strategies using the Seven Quality Control (Seven QC) Tools. The research applied Check Sheet, Histogram, Pareto Diagram, Fishbone Diagram, Scatter Diagram, Flow Chart, and P-Control Chart (P-Chart). Data were collected from January to June 2026, consisting of 3,090 welded joints with 209 defective welds. The results showed an overall defect rate of 6.76%, with porosity as the most dominant defect (38.28%), followed by crack (25.36%) and undercut (17.70%). Pareto analysis indicated that these three defects contributed 81.34% of the total defects. The P-Chart confirmed that the welding process remained statistically under control, while the Fishbone Diagram identified man, machine, method, material, measurement, and environment as the main causes of defects. The proposed improvements include operator training, strict implementation of the Welding Procedure Specification (WPS), preventive maintenance, improved material control, and enhanced inspection procedures to reduce welding defects and improve product quality.